A Study on Hypoglycemic properties of Pterocarpus marsupium Roxb. - Karanjit, N.; Shrestha, U. K.; Ranjitkar, R R. (Journal of Plant Resources, 2009)
Pterocarpus marsupium is a popular ethno-medicinal plant for the treatment of diabeties. In this paper Phytochemical screening, biochemical findings, physicochemical and pharmacognosy studies are reported. The plant extract showed reduction of blood glucose level up to 48%. in rabbits and also showed remarkable inhibition of digestive enzymes (1.23% of amylase, 40% of Trypsin and 20% of lipase). The pharmacognostical character, and Phytochemical/ physicochemical values obtained from this studies will help to identify and check the quality of the plant and its products. Bulletin of the Department of Plant Resources Vol 30, 2008 pp 97-101